Feeling the risk, living the risk: women in themaquiladoras in a border city in Mexico - Mendoza Arvizo, Ulises (2020)
In some parts of the world, women are exposed to atypical acts of violence that include crimes due to war, terrorism, and community violence. Another less prevalent type of violence, not often studied due to its uniqueness, is unpunished female homicides in high-crime cities. Women living under this unusual circumstance may suffer a multitude of effects from “feeling at risk” as a result of direct exposure to community violence and media exposure to female homicide, and by “living the risk” from the effects of domestic violence. These additional effects should be considered when implementing preventive programs in high-crime cities.